1999
DOI: 10.1515/jpem.1999.12.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Factors at Onset Predictive of Lasting Remission in Paediatric Patients with Graves' Disease Followed for at Least Three Years

Abstract: Seventeen pediatric patients (mean age at diagnosis 10 yr and 9 mo +/- 2 yr and 9 mo) with Graves' disease treated with 0.3-0.7 mg/kg/day methimazole and followed for at least three years, during which drug suspension was attempted on attainment of good clinical and metabolic compensation, were retrospectively studied to look for factors predictive of lasting remission present at onset. Lasting remission was defined as a clinical and laboratory picture of euthyroidism lasting at least one year in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 11 publications
2
21
0
1
Order By: Relevance
“…Our study confirmed previous data [39,40] obtained in adults and in children of the absence of influence of fT4 on the outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirmed previous data [39,40] obtained in adults and in children of the absence of influence of fT4 on the outcome.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is reported that TSAb was correlated with the severity of ophthalmopathy in adult Graves' disease [28,29]. The clinical and biological findings of Graves' disease, including ophthalmopathy, are different with age [4,24,25,27,[30][31][32][33], and so it is possible that this difference might be due to age. However, we examined only the presence of ophthalmopathy, and not its severity, hence further evaluation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in long-term treatment with ATD is also being considered in pediatric patients. Many retrospective studies [19,25,31,32] and one prospective study have shown that the duration of medical treatment may be a predictive marker of relapse in juvenile hyperthyroidism. Another prospective study showed that relapse risk of hyperthyroidism decreased with the duration of the first course of ATD and every additional year of ATD therapy was associated with a decrease in the relapse rate [20].…”
Section: Discussionmentioning
confidence: 99%